Linguistic Accommodation: Perception of Malaysian Lawyers - David, Maya Khemlani; Gan, Kah Hui; David, Yoong; Singh, Balbir (2010)
Language Accommodation is “we adjust our communicational behavior to maintain integrity, distance or identity” (Giles and Coupland,1991:66). Do lawyers shift their discourse norms in order to obtain the information required from witnesses in a courtroom? In this study, 24 lawyers were interviewed to elicit the strategies and discourse norms used when questioning the elderly, minors, women and uneducated. The findings are discussed. This is part of a larger study where courtroom discourse is observed to determine if the perceptions of the lawyers are realized in authentic settings. Keywords: accommodation, courtroom, discourse